The Protection of Wages in Contractual Employment Relationships: The International Labour Organisation’s Standards and the Polish Law - Maniewska, Eliza (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
Abstract. The presented study is concerned with the protection of wages in contractual employment relationships on the basis of Polish legislation and the standards of the International Labour Organisation, in particular Convention No. 95. By contractual employment relationships, the author means not only the relations based on an employment contract, but also any contractual relationship that creates on the part of the person performing work the obligation to perform work and on the part of the other party the obligation to pay remuneration for that work. The studies to date have not dealt extensively with the issues of the impact of International Labour Organisation’s (hereafter: ILO) standards on the level of wage protection in Poland. Furthermore, no thorough reflection on possible methods of such an impact and the setting of this issue on a timeline can be found. Research objective: Therefore, in this paper, the author made an attempt to answer the questions of whether, to what extent, and what relevance for wage protection in Poland should be attributed to the ILO standards defined in Convention No. 95, and whether, and how, this has changed over time. Methods: The research is based on a dogmatic analysis of the provisions of the Polish law and Convention No. 95 as well as the documents of the International Labour Organisation and the relevant legal literature. The historical method was applied to examine the transformations of wage protection in Poland. Conclusions: As a result of the analysis, the author concluded that, at the time of the ratification of Convention No. 95, the Polish law met its standards. The departure from these standards was initiated by the economic transformations that took place in Poland after the systemic changes which had begun in 1989. This resulted from the emergence of new forms of employment (provided in civil law) that were devoid of the protection inherent in labour law. An essential factor which made it possible to stop the deterioration of social protection associated with the process was the “anchoring” of Poland in the ILO. Indeed, covering the forms of employment based on civil law by the protection-comprising elements that are proper to labour law was largely due to the need to respect the norm set by the Convention standards. Moreover, the research carried out by the author allowed her to put forward a general thesis that international labour law should be assigned a kind of “fuse” role in addition to other roles it plays. It is because, to a large extent, it prevents a permanent departure from the developed standards of civilisation in the world of labour in situations where states are forced to depart from the standards on a temporary basis.